Prototype Robot Penyemprot Disinfektan Dengan Metode Research And Development - Liesnaningsih Liesnaningsih; Dian Kasoni; Djamaludin Djamaludin (University of Muhammadiyah Tangerang, 2022)
Currently, Indonesia is experiencing a COVID-19 pandemic, so a way is needed to minimize its spread, one of which is by spraying disinfectants. The purpose of this research is to produce an embedded system in the form of a disinfectant spraying robot that is useful for minimizing the spread of Covid-19 with an automatic control system using Arduino Uno and infrared sensors as input. The research method used in this research is research and development. In simple terms, this embedded system will follow the line that has been made, then at a certain time the disinfectant spray will run automatically. The results of testing the infrared sensor and real time clock function well when detecting a black line so that the prototype runs as expected, but the use of an infrared sensor affects the light intensity so that it affects the value of the sensor when conditions are dark and bright.